Ramadan intermittent fasting and its association with health-related indices and exercise test performance in athletes and physically active individuals: an overview of systematic reviews - Hallén, A.; Tomás, R.; Ekstrand, J.; Bengtsson, H.; Van den Steen, E.; Hägglund, M.; Waldén, M. (British Journal of Sports Medicine, 2024)
Objective To systematically review, summarise and appraise findings of published systematic reviews, with/without meta-analyses, examining associations between Ramadan fasting observance (RO), health-related indices and exercise test performances in athletes and physically active individuals.